2015
DOI: 10.25077/jrk.v3i1.102
|View full text |Cite
|
Sign up to set email alerts
|

CHEMICAL COMPOSITION AND ANTIBACTERIAL ACTIVITY OF THE ESSENTIAL OIL OF THE Toona sureni (Blume) Merr

Abstract: The essential oil composition of the Toona sureni (Blume) Merr leaf was analyzed by GC-MS. More than 68 peaks, representing 99.99% of total oil, forty three components were identified, this represents 80.65% of the total oil component. The major components were α-terpinene (9.58%), α-copaene (8.39%), bicyclogermacrene (7.61%), δ-cadinene (6.65%), β-elemene (4.88%), germacrene-D (4.65%), δ-selinene (3.58%), caralene (3.10%), β-caryophyllene (2.88%), α-cubebene (2.82%), δ-gurjunene (2.20%), and (-)-isoledene (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The leaves of the plant was previously studied and several compounds and biologycal activities have been reported due to the presence of tetranortriterpenoid (limonoid) [3]- [4], carotenoid [5]- [8], triterpenoid [9], methyl gallate [10], and essential oil [11]. Methyl gallate exhibited antioxidant activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of the plant was previously studied and several compounds and biologycal activities have been reported due to the presence of tetranortriterpenoid (limonoid) [3]- [4], carotenoid [5]- [8], triterpenoid [9], methyl gallate [10], and essential oil [11]. Methyl gallate exhibited antioxidant activities [10].…”
Section: Introductionmentioning
confidence: 99%
“…The dry biomass of A. platensis and cinnamon powder served as the granules primary sources of antioxidants. The addition of cinnamon powder should have an impact on the FRAP value of A. platensis granules, as study by [34] found that cinnamon bark extract includes an antioxidant component in the form of cinnamaldehyde up to 68.65%. However, because the amount of cinnamon powder applied in this study was so small, only between 0.5 and 1.5% the granule FRAP value was unaffected.…”
Section: The Effect Of Adding Cinnamon and Amylum Mucilage On Emulsio...mentioning
confidence: 99%